Contrasting impacts of an alien invasive shrub on mammalian savanna herbivores revealed on a landscape scale. Issue 6 (June 2017) - Rozen‐Rechels, David; te Beest, Mariska; Dew, L. Alexander; le Roux, Elizabeth; Druce, Dave J.; Cromsigt, Joris P. G. M.
Abstract: Aim: Habitat loss and fragmentation is one of the main drivers of defaunation, that is the loss of large mammals. Biological invasions could be drivers of such phenomenon. However, their impact on large herbivore communities has not been studied to our knowledge. We made use of a landscape‐scale control programme of one of the world's worst invaders, the shrub Chromolaena odorata, as a natural experiment to assess how this alien invader affects habitat use by 14 species of ungulates in an African savanna. Location: Hluhluwe‐iMfolozi Park, KwaZulu‐Natal, South Africa. Methods: At the height of the invasion in 2004, a large‐scale control programme was initiated that successfully reduced densities of C. odorata across the park. We estimated mammalian herbivore habitat and patch use by dung counts and the presence and density of C. odorata along 24 line transects with a total length of 190 km during the peak of the invasion (2004) and a decade after the initiation of a successful control programme (2014). To account for differences in herbivore assemblies between habitats and the preferential invasion of closed savanna woodlands, we analysed the recolonization of previously invaded patches by herbivores based on the change in dung abundance. Results: Herbivore species differed in how they responded to invaded patches of this non‐native shrub. Grazers were the most negatively affected, especially those that avoid predators by running. Browsers were negatively impacted only at the highest invasive shrub densities. Some species, especially bushpig, positively selected invaded patches. Main conclusions: Large herbivores varied in their response to invasion with differences in impact depending on feeding strategy and predator avoidance strategy, but the majority of ungulates responded positively to the removal of this invasive shrub.